Vocational education and training in Croatia : short description - (:unkn) unknown (Publications Office of the European Union, 2020)
This short description contributes to better understanding vocational education and training (VET) in Croatia by providing insights into its main features and highlighting system developments and current challenges in recent years. It is published during the Croatian Presidency in the Council of the EU (first half of 2020). The main focus during the Croatian Presidency is on teachers and trainers who are at the heart of all developmental and reform processes, as promoters and enablers of the new skills needed for the future. Putting words into action, Croatia recently improved many factors in teacher status and has built a system that recognises and rewards excellence in teaching. (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungssteuerung; Bildungsfinanzierung; Bildungspersonal; Kroatien